MEMAHAMI KONSEP DASAR PENDIDKAN LINGKUNGAN : UPAYA MENGHADAPI PERSOALAN KERUSAKAN LINGKUNGAN - Nur Hasanah; Imam Syafi’i; Baharudin; Ali Murtadho (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Increasingly complex environmental degradation, such as pollution, deforestation, and climate change, indicates the existence of an ecological crisis that is not only technical in nature but also moral and educational. Environmental education serves as a strategic instrument in shaping human awareness, attitudes, and behaviors to become more responsible toward environmental sustainability. This paper aims to examine the basic concepts of environmental education as an effort to address environmental degradation, analyze the role of Islamic values as an ethical and spiritual foundation for environmental education, and identify effective environmental education strategies in shaping students’ awareness, attitudes, and behaviors. This study employs a literature review method by analyzing various relevant sources from the perspectives of environmental education and Islamic teachings. The findings reveal that environmental education must be integrated holistically into cognitive, affective, and psychomotor domains. Islamic values, such as the concepts of khalifah (stewardship), amanah (trust), mizan (balance), and the prohibition of fasad (destruction), provide a strong moral and spiritual foundation in developing environmentally responsible character. Environmental education based on Islamic values strengthens students’ motivation, as environmental stewardship is understood as part of worship and religious responsibility. Through integrative, contextual, and role-model-based educational strategies, environmental education is expected to produce a generation that is ecologically aware, morally grounded, and responsible in preserving environmental sustainability.